L’appropriation des politiques publiques du paysage dans les services de l’État ? - Laurent Lelli; Sylvie Paradis (Projets de Paysage)
If the french law about landscape of 1993 left its mark into public policies of the Ministries of Ecology and of Agriculture in particular, it also fostered various professional and institutional practices. The development of an inter-professional network in the Midi-Pyrenees region highlighted the need to question the skills of state employees identified as actively exploited on this theme. It also led to a reflection on identifying the competencies presently mobilized by agents and the eventual needs of additional competencies to better answer public policy demands in which landscape issues are constantly changing, notably as concerns landscape mediation.